Colunas de concreto armado solicitadas por cargas axiais excêntricas - Yamagata, Nobuo (1973)
In this thesis we analyse the behavior of beam-columns with circular or annular cross sections under eccentric longitudinal load. The influence of the changes in shape of the elastic and the non-linearity of the stress-strain curves for both concrete and reinforcement steel is considered through numerical methods. A computer program for the numerical calculation was developed for plotting graphs used in the determination of bearing capacity of columns being studied. The basic assumptions are from the CEB-FIP Recommendations.